Impact of quality of root canal fillings and coronal restorations on the prevalence of apical periodontitis in an adult Saudi subpopulation - Muhammad Zubair Ahmad (Medicina Clínica Práctica)
Objectives: This cross-sectional study aimed to evaluate the prevalence of apical periodontitis among healthy Saudi adult patients and to examine the impact of root canal filling quality and coronal restoration quality on periradicular health. Methods: We used periapical radiographs for this study and categorized the teeth as either diseased or healthy based on the periapical index scores. Two pre-calibrated examiners independently evaluated the radiographs. Any uncertain situation was discussed with another senior examiner. Data were statistically analyzed by applying the Chi-square test or Fisher exact test at a 5% (P < .05) level of significance using IBM SPSS 29.0 software (IBM Corp, Armonk, NY). Results: The overall prevalence of apical periodontitis in endodontically treated teeth was 29.04%. 47.79% of teeth had adequate endodontic treatments. The success rate for teeth with adequate endodontic treatment was significantly higher at 96%, compared to a 48% success rate in teeth with inadequate endodontic treatment (P < .001). Additionally, 70.1% of the teeth had adequate coronal restorations. Teeth with adequate coronal restorations showed a significantly higher success rate at 78.33% compared to the 53.7% success rate of teeth with inadequate coronal restorations (P < .001). Conclusions: The quality of endodontic treatment determines the outcome. Therefore, improvements in root canal treatment procedures are advisable in general and specialist dental practices to enhance periradicular health. The coronal restoration is also an essential component of the overall treatment. The optimal treatment outcome can be achieved with the adequate quality of both endodontic treatment and coronal restoration. Resumen: Objetivos: Este estudio transversal tuvo como objetivo evaluar la prevalencia de periodontitis apical en pacientes adultos sanos saudíes y examinar el impacto tanto de la calidad del relleno del conducto radicular como de la calidad de la restauración coronal en la salud perirradicular. Métodos: Se utilizaron radiografías periapicales para los análisis, y los dientes se clasificaron como sanos o enfermos según el sistema de puntuación del índice periapical. Dos examinadores precalibrados evaluaron las radiografías de manera independiente. Cualquier situación incierta fue discutida con otro examinador sénior. Los datos se analizaron estadísticamente aplicando la prueba de chi-cuadrado o la prueba exacta de Fisher con un nivel de significancia del 5% (p < 0.05) utilizando el software IBM SPSS 29.0 (IBM Corp, Armonk, NY). Resultados: La prevalencia general de periodontitis apical en dientes tratados con conducto radicular fue del 29.04%. El 47.79% de los dientes tenía tratamientos endodónticos adecuados. La tasa de éxito para los dientes con tratamiento endodóntico adecuado fue significativamente mayor, con un 96%, en comparación con la tasa de éxito del 48% en dientes con tratamiento endodóntico inadecuado (p < 0.001). Además, el 70.1% de los dientes tenía restauraciones coronales adecuadas. Los dientes con restauraciones coronales adecuadas mostraron una tasa de éxito significativamente mayor del 78.33%, en comparación con la tasa de éxito del 53.7% de los dientes con restauraciones coronales inadecuadas (p < 0.001). Conclusiones: La calidad del tratamiento endodóntico determina el resultado. Por lo tanto, se recomienda mejorar los procedimientos de tratamiento de conductos radiculares en las prácticas dentales generales y especializadas para mejorar la salud perirradicular. La restauración coronal también es un componente esencial del tratamiento general. El resultado óptimo del tratamiento se puede lograr con la calidad adecuada tanto del tratamiento endodóntico como de la restauración coronal.